What Possible Futures for Africa Post-Covid-19? - A.K. Segobye; A. Sall; E. Picard (The Thinker)
In 1999, a ground-breaking project was initiated by the National Long-Term Perspective Studies (NLTPS) programme, with the financial support of UNDP, aimed at exploring the long-term development prospects of sub-Saharan Africa.